Untangling Blame And Responsibility For Service Delivery And Local Governance Performance: Testing A Grounded Social Accountability Approach In Tanzania - Mdee, Anna; Mushi, Andrew (My University, 2022)
We examine the gap between theory and practice in social accountability mechanisms to improve local governance performance in Tanzania. We do so through drawing on an ethnographic investigation tracing lines of blame and responsibility for service delivery, from individual citizens up to the central state incorporating a total of 340 interviews and 12 focused group discussions. We have two keys findings: Firstly, that there is a wide divergence between formal lines of accountability and where actors direct blame for performance failure in practice. Secondly, building a collective understanding of this divergence provides an effective starting point for intervention to improve performance. Our conclusion is that dominant assumptions on social accountability interventions require significant revision in light of our findings.
Keywords: local governance; Blame; Sociology